Corrosion and Ion Release from Metal Prosthetic Appliances - A. Řeháček; M. Janega; T. Dostálová; L. Vavřičková (Czech Dental Chamber, 2007)
The topic of dental casting alloys in the oral cavity is despite the most modern non-metal technologies still relevant. The knowledge of possible allergenic, mutagenic and cancerogenic impacts of these elements helps us working with patients and makes easier reaching of positive result of the prosthetic or orthodontic treatment. We try to mention at least some of the facts of negative attributes of these materials and possible methods of examination we use to prevent the complications.